Biology of Blattodea and Dermaptera in the Continental Biogeographical Region and Adjacent Areas of European Russia - Victor V. Aleksanov; Alexander B. Ruchin; Nikolai V. Shulaev; Inessa O. Karmazina; Sergey V. Lukiyanov; Evgeniy A. Lobachev; Anna M. Nikolaeva; Mikhail N. Esin (Diversity)
(1) Background: Blattodea and Dermaptera in the temperate forest zone include a limited number of species, some of which are widely distributed and common. However, digital data on their biology remains insufficient. (2) Methods: The surveyed area extends from Kaluga Oblast to Tatarstan and from Vladimir Oblast to Voronezh Oblast. Insects were sampled from 736 plots using various methods, including pitfall traps, beer traps, window traps, pan traps, and sweep nets. (3) Results: The dataset contains 2149 occurrences comprising 18,362 specimens belonging to 5 species of Blattodea and 4 species of Dermaptera. For most occurrences, we recorded the developmental stage (nymph or adult) and the sex (male or female for adults) of the specimens. (4) Conclusions: Three non-synanthropic species are widely distributed and common: Ectobius lapponicus, E. sylvestris, and Forficula auricularia. Ectobius sylvestris is characterized as a true forest species, while E. lapponicus inhabits both forest and grassland habitats. In contrast, F. auricularia is associated with gardens, urban habitats, and some meadows. Ectobius sylvestris exhibits a more pronounced sexual dimorphism concerning the effectiveness of different sampling methods compared to E. lapponicus. Seasonal dynamics of cockroaches and earwigs are described and discussed.